2023
DOI: 10.1073/pnas.2217150120
|View full text |Cite
|
Sign up to set email alerts
|

The smectic Z A phase: Antiferroelectric smectic order as a prelude to the ferroelectric nematic

Abstract: We have structurally characterized the liquid crystal (LC) phase that can appear as an intermediate state when a dielectric nematic, having polar disorder of its molecular dipoles, transitions to the almost perfectly polar-ordered ferroelectric nematic. This intermediate phase, which fills a 100-y-old void in the taxonomy of smectic LCs and which we term the “smectic Z A ,” is antiferroelectric, with the nematic director and polarization oriented parallel to smectic layer planes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…Homogeneous and uniform textures are observed for all temperature/phases as reported earlier in different studies 3,9–11 except that the N F phase shows a sharp texture transition at a temperature of ∼3 °C below the N X –N F transition temperature. This behavior is discussed in Section 2.3.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Homogeneous and uniform textures are observed for all temperature/phases as reported earlier in different studies 3,9–11 except that the N F phase shows a sharp texture transition at a temperature of ∼3 °C below the N X –N F transition temperature. This behavior is discussed in Section 2.3.…”
Section: Resultssupporting
confidence: 84%
“…N X is found to have modulated structure at the nanoscale level, and it exhibits smectic-like SmZ A antiferroelectric behaviour. 9 The nomenclature for the phases of DIO adopted here follows from the works of Nishikawa et al 3 and of Chen et al 9 The N X phase is also termed as the splayed nematic (N S ) by Sebastian et al, 4,10 and as unknown N X by Gorecka et al 11 Hereafter we refer it to N X for the reasons given above. DIO was first synthesized by Nishikawa et al 3 but for the works reported here, it is resynthesized by the group of G. H. Mehl at the University of Hull, Hull, UK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2b-e). 16,45 When the concentration was further increased, phase separation occurred (Fig. S2, ESI †).…”
Section: Resultsmentioning
confidence: 99%